2018
DOI: 10.1002/jca.21623
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic plasma exchange: Experience in a third level hospital, 2013–2016, Lima (Peru)

Abstract: This is the first report of TPE performed in the Peruvian population. The use of an institutional apheresis protocol was beneficial to improve registries in our service and our professional health attention. This study reports a low rate of complications, suggesting that TPE is safe. There is a need to create a multicenter Peruvian apheresis registry to assess the benefits and risks of TPE in Peru.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
3
1
0
Order By: Relevance
“…The observed overall complication rates at our TPE unit (9.4%) were comparable with the recently reported experience in most centres and of the World Apheresis Association (WAA) apheresis registry, ranging from 5% to 12% 10 13 14 19. We observed no complications related to procedures for central venous vascular access, performed under ultrasound-guided by in-house interventional radiologists.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The observed overall complication rates at our TPE unit (9.4%) were comparable with the recently reported experience in most centres and of the World Apheresis Association (WAA) apheresis registry, ranging from 5% to 12% 10 13 14 19. We observed no complications related to procedures for central venous vascular access, performed under ultrasound-guided by in-house interventional radiologists.…”
Section: Discussionsupporting
confidence: 86%
“…At initial set-up of our non-acute TPE unit, we performed TPE for various central and PNS disorders, similar to other recently published data from established centres 13–15. With time, we observed an increase in TPE applications for CNS disorders indications.…”
Section: Discussionsupporting
confidence: 55%
“…The incidence rate of TPE-related AEs varied in different regions, ranging from 3.4 to 9.9% in the US 34,35 and from 10.9 to 60% in other countries outside the US. [36][37][38] The result from our study indicated that the incidence rate of TPE-related AEs in rheumatic treatment was 15.1%, and plasma-induced allergic reaction was the most frequent complication, which is in line with a previous report. 37 Other common AEs included palpitations, dizziness/fatigue, nausea, and hypotension, accounting for 16.4%, 13.6%, 6.4%, and 6.4% in all episodes, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Among our patients who received TPE, the majority started this within the first two weeks, with enough cycles. This treatment was as recommended by the Pan-American Health Organization, the American Apheresis Society (ASFA) and a previous report from the HNDM 10,20,30 . However, not all patients improved during hospitalization, given that the time taken to reach improvement may be longer than the hospital stay 29 .…”
Section: Discussionmentioning
confidence: 99%